Beyond the Game: How Sports Shape Us and Fuel Our Future - Badran, Michalis (Open Schools Journal for Open Science, 2025)
Sports offer far more than physical exercise; they are transformative experiences that enhance our mental, emotional, and social well-being. This talk explores how participation in sports helps cultivate resilience, discipline, leadership, and community. From improving mental health to teaching life skills, the positive impacts of sports extend far beyond the playing field.